The CircularEconomy4Colombia innovation challenge is live - Khader, Taija; Dowling, Kevin (2024)
Bogotá, July 3, 2024 – The CGIAR Accelerate for Impact Platform (A4IP) launches the latest of its science-driven and market-oriented innovation challenges - CircularEconomy4Colombia – with an open call for ambitious innovators.